2010
DOI: 10.1111/j.1365-2958.2010.07383.x
|View full text |Cite
|
Sign up to set email alerts
|

A M23B family metallopeptidase of Helicobacter pylori required for cell shape, pole formation and virulence

Abstract: SummaryThe molecular basis of the regulation of specific shapes and their role for the bacterial fitness remain largely unknown. We focused in this study on the Gram-negative and spiral-shaped Helicobacter pylori. To colonize its unique niche, H. pylori needs to reach quickly the human gastric mucosa, by swimming to and through the mucus layer. For that reason, the specific shape of H. pylori is predicted to be necessary for optimal motility in vivo, and consequently for its colonization ability. Here, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
131
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 28 publications
4
131
0
Order By: Relevance
“…Although overexpression of the Q46H variant did not support helical cell shape generation, it did promote the increased cell length previously observed during overexpression of wild-type Csd4 (10), suggesting additional functions for the protein that do not require enzymatic activity. H. pylori Csd3, an unrelated M23B family metallopeptidase, was shown to have DD-carboxypeptidase activity and can produce tetrapeptides from un-cross-linked pentapeptides (42). In turn, the tetrapeptidecleaving LD-carboxypeptidase Csd6 was recently shown to provide the tripeptide substrate for Csd4.…”
Section: Discussionmentioning
confidence: 99%
“…Although overexpression of the Q46H variant did not support helical cell shape generation, it did promote the increased cell length previously observed during overexpression of wild-type Csd4 (10), suggesting additional functions for the protein that do not require enzymatic activity. H. pylori Csd3, an unrelated M23B family metallopeptidase, was shown to have DD-carboxypeptidase activity and can produce tetrapeptides from un-cross-linked pentapeptides (42). In turn, the tetrapeptidecleaving LD-carboxypeptidase Csd6 was recently shown to provide the tripeptide substrate for Csd4.…”
Section: Discussionmentioning
confidence: 99%
“…Later sequencing of pRJ1004 (NCBI accession no. KC146966) has identified two new genes among the entire 19-gene cluster-pcoF encoding a putative copper-binding protein and pcoG encoding a putative M23B metallopeptidase, an enzyme that has been implicated in pathogenicity (Bonis et al 2010) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…54 Csd3 also seems to possess carboxypeptidase activity, cleaving pentapeptides to generate tetrapeptides. 55 Carboxypeptidase Csd4 trims tripeptides into dipeptides, which can also sever connections between linked PG fragments without directly cleaving the peptide cross-bridge (Fig. 5C).…”
Section: Peptidoglycanmentioning
confidence: 99%
“…54 Therefore, curvature seems more essential to effective motility than helical shape. Csd3 has been independently identified by Bonis et al 55 to possess endo-and carboxypeptidase activity, leading to its annotation as HdpA (Helicobacter DD-peptidase A). However, this group found that HdpA controls additional aspects of cell morphology beyond modifying PG, including cell diameter, length, and formation of a single pole.…”
Section: Peptidoglycanmentioning
confidence: 99%
See 1 more Smart Citation